PEMBERDAYAAN GURU MELALUI PELATIHAN TEKNOLOGI TEACHY AI UNTUK MENINGKATKAN EFEKTIVITAS PEMBELAJARAN INTERAKTIF - Syaiful Hidayat; Arham Rahim; Irfan; Sofia Anastasya (Makapande Mengabdi: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
Advancements in digital technology have led to significant transformations in the field of education, one of which is the integration of artificial intelligence (AI). AI offers the potential to deliver interactive, adaptive, and personalized learning experiences. However, many educators still face considerable challenges in incorporating AI into their teaching practices, primarily due to limited digital literacy and insufficient access to professional development opportunities.This community engagement initiative was designed to empower educators and enhance their competencies in educational technology through a structured training workshop focused on the use of Teachy AI—an AI-based platform specifically developed to support teaching and learning processes. The workshop involved ten participants, comprising both teachers and students. The outcomes of the activity demonstrated a marked improvement in participants’ understanding and practical skills, as evidenced by comparative analysis of pre-test and post-test results. Educators who were previously only familiar with general AI tools such as ChatGPT or CanvaAI gained proficiency in using Teachy AI to develop interactive educational media, streamline administrative tasks, and foster more meaningful engagement with students.